Educational factors influencing ethnic identity of secondary school Chinese students in Malaysia / Ho Pei Yao - Ho , Pei Yao (2018)
The complexity of Chinese education in the making of Chinese ethnic identity continues to be highly debated issues in the ethnically diverse Malaysian society even after nearly six decades of independence. By employing social psychological approach, this research examined the Malaysian Chinese secondary school students’ ethnic identity, the issues of Chinese language and education, as well as the relationship between the two variables of the Malaysian Chinese secondary school students’ ethnic identity and Chinese language and education, from the perspectives of the secondary school students themselves. Applying the research theoretical framework based on Social Identity Theory (Tajfel, 1974), Theory of Identity Development (Erikson, 1968) and Personality and Social Structure Perspective model (PSSP) (Côtѐ, & Levine, 2002), the context-bounded construct of the Malaysian Chinese secondary school students’ ethnic identity is investigated within the current Malaysian educational contexts. Quantitative survey method with Likert Scale and open-ended questions was employed for data collection and analysis. Stratified sampling method was conducted in selected secondary schools from five regions in Malaysia with a total of 1342 respondents. The selected secondary schools consisted of National Secondary Schools (NSS), National Type Secondary Schools (NTSS) and Independent Chinese Secondary Schools (ICSS). The correlation between Chinese language and education with Chinese students’ ethnic identity is confirmed in this research albeit the correlations were found for different dimensions of ethnic identity with the specific educational factors. iv With the comparison on the typology of the modified education category from the model of Chinese identity and Chinese education (Tan, 1988a), statistical findings indicated that NSS students have showed a higher level of ethnic identity than students in the ICSS and NTSS. More specifically, the highest scores were found for NSS students in their composite index of Overall Ethnic Identity Measure (OEIM) as well as the dimensions of Affirmation and Belonging (A&B) and Exploration and Individual-based Interpretation (E&IbI). In terms of Chinese language and education, the students’ perspectives are manifold, with prevalent usage and preference of Chinese language in their everyday life and general positive views and attitudes in maintaining and passing down Chinese education. In causal relationship, the NSS students’ ethnic identity is predicted by more micro level educational factors whereas the ICSS and NTSS students’ ethnic identity is predicted by more macro level educational factors. The research findings highlighted the effects of each education contextual factors by school type but comprehensive Chinese mother tongue education predicted the students’ ethnic identity from all education categories. This research indicated the importance of the immediate social contextual factors in constructing the Malaysian Chinese secondary school students’ ethnic identity as well as the societal beliefs of Chinese language and education as an ethnic representation within the context of Malaysian multi-ethnic setting. Considering that ethnic identity is contextually determined, the current educational system with different secondary educational tracks should be re-examine to assign Chinese language and education with new meaning and better understanding, for the multi-ethnic amalgamation and national integration.